Pelatihan dan Pendampingan Pembuatan Eco Enzyme dan Pemanfaatan Limbah Plastik bagi Guru dan Siswa SDK Penabur 6 Kelapa Gading - Suhartono, Sugi; Meiden, Carmel; Aleksander, Gabriel; Adi Saputro, Jevontius (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Eco Enzyme is a fermentation solution from organic waste such as fruit and vegetable waste, sugar and water. This environmentally friendly enzyme is in liquid form which has many benefits ranging from agriculture, household to pets. Implementing this Eco Enzyme is to find out whether it has an effect on plant growth and to find out the dose that gives the best results. However, apart from being a powerful organic fertilizer, Eco Enzyme have a versatile function in making knick-knacks from used goods, especially plastic waste which is difficult to decompose in the environment. This approach aims to educate students about the importance of recycling and creativity in managing plastic waste. The aim of this program is more efficient assistance in increasing students understanding of the manufacturing process and benefits of Eco Enzyme and inspiring student creativity in recycling plastic waste into useful products.